The Legal Protection for Land Rights Holders against Different Locations of Land Objects - Poni Agustin; Widhi Handoko (Sultan Agung Notary Law Review, 2022)
The importance of land ownership rights, the State in this case is represented by the National Land Agency (BPN) plays an important role in ensuring certainty and legal force for land rights holders. In the issuance of certificates, of course there are rights, checking the location of land parcels, and other procedures that must be followed. In this writing, the certificate issued by BPN experienced a discrepancy between the rights, in this case the Sale and Purchase Deed, so that the juridical data and physical data experienced differences. The existence of differences in physical and juridical data causes the certificate to be questioned for its legal certainty and strength. Efforts against the existence of administrative defects in certificates can be taken by means of, among others, administrative and judicial efforts. The problems in the research include how to protect the law for holders of land rights against differences in the location of land objects in the sale and purchase deeds and certificates, as well as about the legal consequences of these deeds and certificates. This study uses a normative juridical research method with descriptive research specifications where this study aims to describe (describe) a problem in a certain area or at a certain time. This study uses secondary data sources which are divided into primary legal materials, secondary and tertiary legal materials. The research results that have been collected are then analyzed qualitatively.